Correlaciones moleculares, clínicas y serológicas de los alfaherpesvirus de Rumiantes, con especial referencia al HVB-1 (1999)
ABSTRACT: Although the complete sequence of the HVB-1 (prototype of study if the Alfaherpesviruses of ruminants) is available, the relationship among the alfaherpesvirus has been poorly characterized. This becomes an obstacle for the differential diagnosis if this viruses and for the filogenetic analysis among them. In this review, we want to present some of the information which has been published recently on genomic, clinic and serological comparisons among the agents of this viral group, with special emphasis on BHV-1. The data presented are compatible with our hypothesis that IBR strains circulating in Colombia may be less virulent.